Experience of the initial counselling session by counsellors and their adolescent clients - Beuthin, Madeleine Barclay (My University, 2014)
The literature suggests that one of the challenging aspects of working with adolescents is in engaging with them in the initial stages of counselling.Thus the focus of the study was the engagement process between client and counsellor in a first session. It was hoped that by gaining a rich understanding of this process it would help to guide and develop the skills of counsellors working with adolescents at the Family Life Centre and elsewhere. A group of twenty adolescent clients, together with their counsellors, were involved in a qualitative study using a fieldwork design.Theory driven data collection was used and both clients and counsellors were interviewed after their first session, using semi-structured interview schedules. Content Analysis was used to analyse the data. This process yielded themes and patterns associated with the different dimensions of the engagement process, including the therapeutic alliance, client participation,involvement and motivation, as well as clients' and counsellors' perceptions of obstacles and facilitating factors in the engagement process.